Republic of Estonia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper and Statistical Appendix analyzes the progress made by Estonia since independence. It takes stock of the developments in the banking system and describes how the number of banks in Estonia has been reduced through a series of bankruptcies and mergers from 41 in 1992 to 5 by end 1998. The paper explores nonbank financial sector developments. The paper also describes a composite index of coincidence indicators and tests how well it has tracked recent developments in Estonia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet